Infanzia e prima adolescenza di Josemaría Escrivá: Barbastro 1902-1915. Contesti, eventi biografici, stato delle ricerche e prospettive di approfondimento / Childhood and adolescence of Josemaría Escrivá: Barbastro 1902-1915: Context, biographical details, progress report and research tendencies - Carlo Pioppi (Studia et Documenta)
This article presents biographical data relating to the first 13 years of the life of Josemaría Escrivá which were spent in Barbastro. The author puts the events in their historical context and describes the influence of this period on Josemaría’s life and on Opus Dei. Moreover, a “status quaestionis” of the subject is presented, accompanied by a bibliography and topics which need to be explored further.